2017
DOI: 10.1016/j.bone.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Bone fracture nonunion rate decreases with increasing age: A prospective inception cohort study

Abstract: A logistic model predicted nonunion with reasonable accuracy (AUC=0.725). Within the Medicare population, nonunion patients were younger than patients who healed normally. Fracture was associated with increased risk of death within 1year of fracture (p<0.0001) in 14 different bones, confirming that geriatric fracture is a major public health issue. Comorbidities associated with increased risk of nonunion include past or current smoking, alcoholism, obesity or morbid obesity, osteoarthritis, rheumatoid arthriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 36 publications
1
78
2
1
Order By: Relevance
“…Even though obesity was thought to be a protecting factor for the skeleton due to its association with increased bone mineral density [23], it has been recently shown that obesity is associated with increased prevalence of bone fractures [24]. A recent prospective cohort study using data from 56,492 fractures of Medicare patients identified obesity as a risk factor for fracture nonunion [25]. The reduced bone turnover seems to be related with progressive insulin resistance induced by weight gain [26].…”
Section: Discussionmentioning
confidence: 99%
“…Even though obesity was thought to be a protecting factor for the skeleton due to its association with increased bone mineral density [23], it has been recently shown that obesity is associated with increased prevalence of bone fractures [24]. A recent prospective cohort study using data from 56,492 fractures of Medicare patients identified obesity as a risk factor for fracture nonunion [25]. The reduced bone turnover seems to be related with progressive insulin resistance induced by weight gain [26].…”
Section: Discussionmentioning
confidence: 99%
“…The US Food and Drug Administration (FDA) define a nonunion as a fracture that does not heal within nine months and reports nonunion occurring in 1 out of 40 fractures (20). A lack of healing progression within three consecutive months is the clinical definition of a delayed union (21).…”
Section: Discussionmentioning
confidence: 99%
“…An inadequate blood supply may also originate from central cardiovascular (stroke, cardiac arrest) insufficiency and peripheral vascular (i.e. atherosclerosis, venous thrombosis) diseases [43] (Figure 3).…”
Section: Trauma Surgerymentioning
confidence: 99%